2015
DOI: 10.7717/peerj.807
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence between populations of feral and domestic forms of a mosquito disease vector assessed by transcriptomics

Abstract: Culex pipiens, an invasive mosquito and vector of West Nile virus in the US, has two morphologically indistinguishable forms that differ dramatically in behavior and physiology. Cx. pipiens form pipiens is primarily a bird-feeding temperate mosquito, while the sub-tropical Cx. pipiens form molestus thrives in sewers and feeds on mammals. Because the feral form can diapause during the cold winters but the domestic form cannot, the two Cx. pipiens forms are allopatric in northern Europe and, although viable, hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 82 publications
0
27
0
Order By: Relevance
“…The only other transcriptomic study of Cx. pipiens f. molestus to date found that the relationship between species was sufficiently close to obtain reliable mapping results [ 26 ]. Both species belong to the Cx.…”
Section: Discussionmentioning
confidence: 99%
“…The only other transcriptomic study of Cx. pipiens f. molestus to date found that the relationship between species was sufficiently close to obtain reliable mapping results [ 26 ]. Both species belong to the Cx.…”
Section: Discussionmentioning
confidence: 99%
“…As a supplement to publicly available data, we also sequenced the genomes of three additional Culex samples. One of these was a single adult female from a laboratory strain of molestus that derived from New York City, USA [43]. The second was an adult female pipiens, reared from a larva collected in an oviposition trap placed in a wooded area on the campus of Montclair State University in Passaic County, New Jersey, USA.…”
Section: Datamentioning
confidence: 99%
“…Among our pipiens and molestus samples, it is impossible to determine if many of the taxonomic designations are incorrect within the context of this study. Nonetheless, all eastern USA molestus samples were determined to be autogenic [43,53], as was the sample from Germany [41]. The molestus from the western USA and Russia were taxonomically assessed using molecular methods [42].…”
Section: Limitations Of This Studymentioning
confidence: 99%
“…A comparison of Cx. pipiens form pipiens and form molestus transcriptomes revealed that odorant-binding proteins were statistically overrepresented in the subset of genes with the highest divergence rates (Price and Fonseca, 2015). Thus, evolutionary changes to the olfactory periphery, even at the molecular level, can significantly impact host preference.…”
Section: Evolution Of Mosquito Orsmentioning
confidence: 99%
“…gambiae, has convergently evolved several ORs responsive to sulcatone (Carey et al, 2010), suggesting that host preference is driven by selection for OR profiles in the peripheral nervous system. To add to the complexity of peripheral nervous system 'players', the evolution of which can contribute to host-preference phenotypes, recent comparative proteomic and transcriptomic studies have revealed differences in the abundance of odorantbinding proteins of closely related mosquitoes with divergent host preferences (Rinker et al, 2013;Price and Fonseca, 2015;Iovinella et al, 2017). One example comes from comparisons of species in the An.…”
Section: Evolution Of Mosquito Orsmentioning
confidence: 99%